ANORTHITE-RICH CHONDRULES IN CR AND CH CARBONACEOUS CHONDRITES: GENETIC LINK BETWEEN CALCIUM-ALUMINUM-RICH INCLUSIONS AND FERROMAGNESIAN CHONDRULES - Krot A.N.; Keil K. (My University, 2002)
Anorthite-rich chondrules in CR and CH carbonaceous chondrites consist of magnesian low-Ca pyroxene and forsterite phenocrysts, FeNi-metal nodules, interstitial anorthite, Al-Ti-Cr-rich low-Ca and high-Ca pyroxenes, and crystalline mesostasis composed of silica, anorthite and high-Ca pyroxene. Three anorthite-rich chondrules contain relic calcium-aluminum-rich inclusions (CAIs) composed of anorthite, spinel, ±Al-diopside, and ± forsterite. A few chondrules contain regions which are texturally and mineralogically similar to magnesian (type I) chondrules and consist of forsterite, low-Ca pyroxene and abundant FeNi-metal nodules. Anorthite-rich chondrules in CR and CH chondrites are mineralogically similar to those in CV and CO carbonaceous chondrites, but contain no secondary nepheline, sodalite or ferrosilite. Relatively high abundances of moderately-volatile elements such as Cr, Mn and Si in the anorthite-rich chondrules suggest that these chondrules could not have been produced by volatilization of the ferromagnesian chondrule precursors or by melting of the refractory materials only. We infer instead that anorthite-rich chondrules in carbonaceous chondrites formed by melting of the reduced chondrule precursors (olivine, pyroxenes, FeNi-metal) mixed with the refractory materials, including relic CAIs, composed of anorthite, spinel, high-Ca pyroxene and forsterite. The observed mineralogical and textural similarities of the anorthite-rich chondrules in several carbonaceous chondrite groups (CV, CO, CH, CR) may indicate that these chondrules formed in the region(s) intermediate between the regions where CAIs and ferromagnesian chondrules originated. This may explain the relative enrichment of anorthite-rich chondrules in 16O compared to typical ferromagnesian chondrules (Russell et al., 2000).